Vessel traffic disrupts walrus vocal behavior in a proposed marine protected area - Coppolaro, Veronica L. M.; Ausen, Emma L.; Loseto, Lisa L.; Marcoux, Marianne (Frontiers in Marine Science, 2025)
Vessel traffic and underwater noise pollution are increasing in the Arctic. Marine mammals are sensitive to underwater noise from vessels which can negatively impact them at the individual and population levels. The marine region of Southampton Island, Nunavut, Canada, is a recognized key area for many marine mammal species and is under consideration to become a marine protected area. Given the increase in vessel traffic in the region, this study explores the potential impact of vessel traffic noise on the vocal behavior of walruses and belugas. This represents the first study to investigate walrus vocal behavior during exposure to vessels. Underwater acoustic data were collected near Southampton Island from June to November 2018. Vessel movements were tracked using the Automatic Identification System (AIS) data and compared with underwater recordings to identify noise sources by vessel type (ship or motorboat). Generalized linear mixed models were used to assess changes in walrus vocalization rates before, during, and after vessel encounters across vessel type. The results showed that walrus vocalization rates decreased during and after vessel encounters and were significantly lower in the presence of ships than motorboats. Belugas were never recorded during motorboat transits, which may indicate avoidance behavior. However, there was not enough data to investigate this hypothesis further. Our findings demonstrate that vessel traffic influences walrus vocal behavior and highlight the need for updated maritime navigation mitigation measures in the study area.